The Influence of Liquidity, Leverage, and Asset Growth Towards the Profitability of the Company on the Idx Mes Bumn 17 Index - Pamuji, Rizti Mugi; Santoso, Suryo Budi; Fakhruddin, Iwan (Asian Journal of Management Analytics, 2025)
The purpose of this research was to examine the Impact of liquidity, leverage, and asset growth on Profitability as proxied by The Return On Assets (ROA) of the companies in IDX MES BUMN 17 indexregistered on The years 2021-2023 of the Indonesian Stock Exchange. Population with in research was 20 companies, while the sample was determined by purposive sampling technique, so it was obtained 12 companies with 36 data that matched the criteria. The research used analysismethod of multiple linear regression with SPSS software. Results ofthisstudyshowedthat leverage has a significant negative effect on Profitability, and asset growth has a positive significant impact on profitability.